Strengthening The Pedagogical Competency of Vocational School Mathematics Teachers In Developing Project-Based Learning - Ratna Yulis Tyaningsih; Baidowi Baidowi; Sripatmi Sripatmi; Laila Hayati; Ni Made Intan Kertiyani (Kontribusi: Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Project-based learning (PjBL) become one of the learning models which suitable for vocational school students. However, teaching materials that facilitate this learning are still limited. To answer this problem, community service activities in the form of seminars were carried out to strengthen the pedagogical competence of vocational school mathematics teachers in Central Lombok district in developing project-based learning teaching material content. The specific aim of this activity wat the vocational school mathematics teachers in Central Lombok district has a good understanding of designing types of projects and the steps for implementing this learning in the classroom. This activity was carried out by 15 mathematics teachers at 11 vocational schools in Central Lombok district as partner schools. The material discussed includes theory regarding the PjBL model. The results obtained in the questionnaire show that this seminar activity was able to provide teachers with knowledge regarding PjBL theory, selecting appropriate projects for students and how to implemented this learning in the classroom.